Robotic reverberation mapping of the broad-line radio galaxy 3C 120. Issue 3 (25th July 2020) - Hlabathe, Michael S; Starkey, David A; Horne, Keith; Romero-Colmenero, Encarni; Crawford, Steven M; Valenti, Stefano; Winkler, Hartmut; Barth, Aaron J; Onken, Christopher A; Sand, David J; Treu, Tommaso; Diamond-Stanic, Aleksandar M; et al.
ABSTRACT: We carried out photometric and spectroscopic observations of the well-studied broad-line radio galaxy 3C 120 with the Las Cumbres Observatory (LCO) global robotic telescope network from 2016 December to 2018 April as part of the LCO AGN Key Project on Reverberation Mapping of Accretion Flows. Here, we present both spectroscopic and photometric reverberation mapping results. We used the interpolated cross-correlation function to perform multiple-line lag measurements in 3C 120. We find the H γ, He ii λ4686, H β, and He i λ5876 lags of τ _cen = 18.8_-1.0^+1.3, 2.7_-0.8^+0.7, 21.2_-1.0^+1.6, and 16.9_-1.1^+0.9 d, respectively, relative to the V -band continuum. Using the measured lag and rms velocity width of the H β emission line, we determine the mass of the black hole for 3C 120 to be M=(6.3^+0.5_-0.3)× 10^7 (f/5.5) M⊙ . Our black hole mass measurement is consistent with similar previous studies on 3C 120, but with small uncertainties. In addition, velocity-resolved lags in 3C 120 show a symmetric pattern across the H β line, 25 d at line centre decreasing to 17 d in the line wings at ±4000 km s −1 . We also investigate the inter-band continuum lags in 3C 120 and find that they are generally consistent with τ ∝ λ 4/3 as predicted from a geometrically thin, optically thick accretion disc. From the continuum lags, we measure the best-fitting value τ0 = 3.5 ± 0.2 d at λ _0 = 5477 A . It implies a disc size a factor of 1.6 times larger than prediction from the standard disc model with L / L Edd = 0.4. This is consistent with previous studies in which larger than expected disc sizes were measured.